Impact of combined transient plasma/heat loads on tungsten performance below and above recrystallization temperature. (30th October 2015) - Loewenhoff, Th.; Bardin, S.; Greuner, H.; Linke, J.; Maier, H.; Morgan, T. W.; Pintsuk, G.; Pitts, R.A.; Riccardi, B.; De Temmerman, G.
Abstract: The influence of recrystallization on thermal shock resistance has been identified as an issue that may influence the long term performance of ITER tungsten (W) divertor components. To investigate this issue a unique series of experiments has been performed on ITER divertor W monoblock mock-ups in three EU high heat flux facilities: GLADIS (neutral beam), JUDITH 2 (electron beam) and Magnum-PSI (plasma beam). To simulate ITER mitigated edge localised modes, heat fluxes between 0.11 and 0.6 GW m −2 were applied for Δ t   <  1 ms. Two different base temperatures, T base   =  1200 °C and 1500 °C, were chosen on which ~18 000/100 000 transient events were superimposed representing several full ITER burning plasma discharges in terms of number of transients and particle fluence. An increase in roughening for both e-beam and plasma loaded surfaces was observed when loading during or after recrystallization and when loading at higher temperature. However, regarding the formation of cracks and microstructural modifications the response was different for e-beam and plasma loaded surfaces. The samples loaded in Magnum-PSI did not crack nor show any sign of recrystallization, even at T base   =  1500 °C. This could be a dynamic hydrogen flux effect, because pre-loading of samples with hydrogen neutrals (GLADIS) or without hydrogen (e-beam JUDITH 2) did not yield this result. These results show clearly that the loading method used when investigating and qualifying the thermal shock performance of materials for ITER and future fusion reactors can play an important role. This should be properly accounted for and in fact should be the subject of further R&D.